Asuhan Kebidanan pada Ny. “Y” dengan Anemia Ringan di RSKD Ibu dan Anak Pertiwi Makassar Tahun 2024 - Jumriana Ibriani; Nirwana Nirwana; Fitri Kumalasary; Nurul Fitrahminarsih N (NAJ Nursing Applied Journal, 2025)
Anemia in pregnancy is a condition in which the hemoglobin level in the blood is below normal. This condition is caused by a decrease in the number of red blood cells or a decrease in hemoglobin levels, which results in a decrease in the oxygen transport capacity needed by important organs for both the mother and the fetus. Types of research and techniques for obtaining primary and secondary data. The subject of the study, pregnant women in Mrs. Y, 32 years old, G6P4A1, gestational age 39 weeks 3 days, single fetus, alive, intrauterine, with the lowest part of the head, experiencing mild anemia. Place of research, at RSKD Ibu dan Anak Pertiwi Makassar. Conclusion of the research results, From the Midwifery Care given to Mrs. Y with Mild Anemia at RSKD Ibu dan Anak Pertiwi Makassar, using 7 steps Varney went smoothly and there was no potential diagnosis.